Biomechanical and functional properties of trophoblast cells exposed to Group B Streptococcus in vitro and the beneficial effects of uvaol treatment - Botelho, R.M.; Tenorio, L.P.G.; Silva, A.L.M.; Tanabe, E.L.L.; Pires, K.S.N.; Gonçalves, C.M.; Santos, J.C.; Marques, A.L.X.; Allard, M.J.; Bergeron, J.D.; Sebire, G.; Silva, E.C.O.; et al. (Biochimica et biophysica acta. General subjects, 2019)
Group B streptococcus (GBS) is the main bacteria that infects pregnant women and can cause abortion and chorioamnionitis. The impact of GBS effects on human trophoblast cells remains largely elusive, and actions toward anti-inflammatory strategies in pregnancy are needed. A potent anti-inflammatory molecule, uvaol is a triterpene from olive oil and its functions in trophoblasts are unknown. We aimed to analyze biomechanical and functional effects of inactivated GBS in trophoblast cells, with the addition of uvaol to test potential benefits. HTR-8/SVneo cells were treated with uvaol and incubated with inactivated GBS. Cell viability and death were analyzed. Cellular elasticity and topography were accessed by atomic force microscopy. Nitrite production was evaluated by Griess reaction. Nuclear translocation of NFkB p65 was detected by immunofluorescence and Th1/Th2 cytokines by bead-based multiplex assay. GBS at 108 CFU increased cell death, which was partially prevented by uvaol. Cell stiffness, cytoskeleton organization and morphology were changed by GBS, and uvaol partially restored these alterations. Nuclear translocation of NFkB p65 began 15 min after GBS incubation and uvaol inhibited this process. GBS decreased IL-4 secretion and increased IL-1β, IFN-γ and IL-2, whereas uvaol reverted this. The increased inflammation and cell death caused by GBS correlated with biomechanical and cytoskeleton changes found in trophoblast cells, while uvaol was effective its protective role. Uvaol is a natural anti-inflammatory product efficient against GBS-induced inflammation and it has potential to be acquired through diet in order to prevent GBS deleterious effects in pregnancy. [Display omitted] •GBS increased trophoblast cell death and altered their morphology•GBS induced changes in trophoblast cytoskeleton and reduced membrane stiffness•GBS induced NFkB translocation to the nuclei, nitrite and Th1 cytokines secretion•Uvaol prevented cell deatl and increased cell stiffness•Uvaol delayed GBS-induced NFkB translocation and reduced Th1 cytokines secretion